2004
DOI: 10.1080/00986440490472715
|View full text |Cite
|
Sign up to set email alerts
|

DYNAMIC FUZZY ADAPTIVE CONTROLLER FOR pH

Abstract: Control of pH processes is very difficult due to nonlinear dynamics, high sensitivity at the neutral point, and changes in the concentrations of known or unknown chemical species. In this study, a dynamic fuzzy adaptive controller (DFAC) with a new inference mechanism is proposed and applied for the control of pH processes. The DFAC consists of a low-level basic control phase with a minimum rule base and a high-level dynamic learining phase with an updating mechanism to interact and modify the control rule bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…One of the approaches proposed use of material balances and electroneutrality relations on component ions for dynamic pH process model and time-optimal pH control [4,5]. Because of its simplicity, this model has been used by many researchers as a platform to introduce AI based control techniques [6][7][8]. In addition, dynamic pH models based on reaction invariant and strong acid equivalent were designed for various nonlinear and adaptive control schemes [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…One of the approaches proposed use of material balances and electroneutrality relations on component ions for dynamic pH process model and time-optimal pH control [4,5]. Because of its simplicity, this model has been used by many researchers as a platform to introduce AI based control techniques [6][7][8]. In addition, dynamic pH models based on reaction invariant and strong acid equivalent were designed for various nonlinear and adaptive control schemes [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Babuska et al implemented a fuzzy self-tuning PI controller for a small-scale fermentation system successfully. Venkateswarlu and Anuradha formulated a dynamic fuzzy adaptive controller (DFAC) and found that DFAC provides improved performance for the control of highly nonlinear pH processes compared to conventional PI, fuzzy, and adaptive PID controllers.…”
Section: Introductionmentioning
confidence: 99%